Hybridities and awkward constructions in Philippine locavorism: reframing global-local dynamics through assemblage thinking. (14th March 2020) - Montefrio, Marvin Joseph F.; De Chavez, Jeremy C.; Contreras, Antonio P.; Erasga, Dennis S.
ABSTRACT: In the last six years, there has been an emergence of food retail establishments that claim to advocate and practice locavorism in Manila, capital of the Philippines. Based on three years of field research and new media analysis, we observed that the Manila adaptation of locavorism has striking similarities to and notable differences from its Western cognates, manifesting as complex amalgamations of local-global discourses and materialities. We examine this articulation as an "assemblage" that manifests as hybridities, a product of the combination of Filipino and Western discursive elements and material practices, and as "awkward constructions", a combination of disengaged consumers, haphazard combinations of local and imported ingredients, and exclusionary consumer spaces. In this distinctive formation, culinary bricoleurs – restaurant owners and chefs – "make do", rearrange and experiment with a variety of discursive and material components available from the local and the global to create a largely fragmented and messy local food enterprise. We attribute the contingence of this assemblage to the colonial history and post-colonial conditions of the Philippines, where associated power dynamics have shaped locavorism subjects as they negotiate the continued influence of Western culinary culture and navigate the competitive world of food business.